A Paraneoplastic Syndrome Characterized by Extremity Swelling with Associated Inflammatory Infiltrate Heralds Aggressive Transformation of Myelodysplastic Syndromes/Myeloproliferative Neoplasms to Acute Myeloid Leukemia: A Case Series - James K. Mangan; Selina M. Luger (Case Reports in Hematology)
There has been a long history of reports describing a variety of paraneoplastic phenomena associated with myelodysplastic syndromes, particularly those with autoimmune manifestations. We report here a series of patients with an antecedent myelodysplastic syndrome (MDS) or myeloproliferative neoplasm (MPN) that underwent aggressive transformation to acute myeloid leukemia (AML). In each case, the transformation to AML was preceded by an inflammatory syndrome characterized by unilateral extremity swelling and an associated inflammatory skin infiltrate, as well as other signs of inflammation, including profound hyperferritinemia without evidence of a hemophagocytic syndrome. We suggest that such an inflammatory syndrome may herald aggressive transformation of MDS/MPN to AML. Patients with known MDS/MPN who present with these features may benefit from early bone marrow examination to assess disease status. Early intervention with corticosteroids in select patients may result in improvement or resolution of the symptoms and permit intensive therapy for AML to be delivered.